Heavy metals in marsh clam (Polymesoda expansa) and green mussel (Perna viridis) along the northwest coast of Sabah, Malaysia - Noor Diani Bambang Dwi Harsono; Julian Ransangan; Delta Jenetty Denil; Kar, Soon Tan (Borneo Marine Research Institute, 2017)
Bivalves are known for their ability to accumulate contaminants such as heavy metals. This allows them to be widely used as bioindicator in monitoring of heavy metals in the marine environment. This study was conducted to determine the levels of heavy metals, namely Copper (Cu), Chromium (Cr), Nickel (Ni), Lead (Pb), Arsenic (As), Zinc (Zn) and Manganese (Mn) in marsh clams (Polymesoda expansa) and green mussels (Perna viridis) along the northwest coast of Sabah (Marudu Bay, Ambong Bay, and Mengkabong). The results showed that As (5.1 to 12.8 μg/g) and Mn (33.5 to 116.0 μg/g) concentrations in both marsh clams and green mussels collected from all the sampling stations along the northwest coast of Sabah were much higher than the permissible limit set by the Ministry of Health Malaysia and FAO/ WHO. Similarly, concentration of Zn (265.8 to 535.9 μg/g) in marsh clams from all the sampling areas and that of Cr (53.9 μg/g) in green mussel collected from Marudu Bay were also much higher than the permissible limits. The data also suggested that marsh clams accumulated higher Pb and Zn, whereas green mussels tend to contain higher concentrations of Cr, Cu and Ni. Since bivalves are an important protein source for the local population, a regular monitoring of all edible bivalve species should be conducted so that consumers can be advised about the toxicological and health risks due to consumption of bivalves.